Edukasi dan Pendampingan Anak-anak tentang PHBS dalam Perspektif Kesehatan Lingkungan di Dukuh Daleman, Jomboran, dan Kadekrowo - Musfirah Musfirah; Amalia Savitri Damaratri; Nur Rahmayani Laelin; Efrida Siti Alifia; Wisi Unggul Pertiwi (Universitas Mathla'ul Anwar Banten, 2021)
EDUCATIONAL AND MENTORING CHILDREN ABOUT PHBS IN ENVIRONMENTAL HEALTH PERSPECTIVES IN DALEMAN, JOMBORAN AND KADEKROWO HAMLET. Clean and Healthy Living Behavior (CHLB) is a health program in Indonesia. Poor handwashing with soap and waste management becomes an issue that cannot be optimally addressed which is assessed from an environmental health perspective. Poor behavior can lead to the emergence of environmental health-based diseases such as diarrhea, helminthiasis. Maintaining CHLB must be early introduced in children. Children are highly vulnerable to the negative health consequences associated with many environmental exposures. Community Service aims to provide early health education and CHLB assistance on how to wash hands properly, waste management for children in Daleman, Jomboran, and Kadekrowo hamlet. The method used in counseling, training, and assistance in the sticker-type rubbish media usage and involvement cooperation based on routine community service work. Activities carried out on 5th, 9th, 11st, 17th, 19th, 20th, and 26th February 2020. The result of these activities was a positive impact for children to make it a habit to wash their hands with soap promptly and carry out waste management and know disease based on environmental health. Children's participation rates were very high in mentoring programs. Children can stimulate other communities starting from their neighborhoods routinely and sustainably.